Fatores ambientais e espacias que controlam a variação na composição das assembleias de fitoplâncton em reservatório - Assis, Gisele Fernanda Pereira (2018)
One of the major aim of ecology studies is to understand the distribution of species and variation in its composition. The mechanisms responsible for this change help to clarify the factors that affect the functioning of aquatic and terrestrial ecosystems. In this context, three factors are the main filters that determine the occurrence of species in a local (dispersion, niche, interactions) in the different ecosystems. The addition of space, through spatial filters, is also an important component that controls the variation in assemblages, in addition to environmental conditions. Recent studies have used the predictors of environmental factors and spatial (geographical distance between sites) to explain the variation in the structure of biological assemblages. The construction of reservoirs for the implantation of hydroelectric plants has been growing lately, promoting physical and chemical changes in the water that consequently alter aquatic diversity. Thus, the objective of this work was to evaluate the role of environmental and spatial factors in the variation of the phytoplankton composition of a tropical reservoir. Sampling was carried out in 40 sites distributed by the Manso reservoir in Mato Grosso. The physical- chemical variables were measured simultaneously with the samples of the organisms. To quantify the effects of environmental and spatial variables on the composition of phytoplankton species, I used Partial Redundancy Analysis (pRDA). A total of 130 species were recorded. Variation partitioning showed that the spatial component was more important for the variation of the evaluated composition than the environmental variables and that the north and south arms are significantly different in composition. One possible reason that may explain the high spatial effect for these organisms is the lake configuration. This has different sides and a great spatial extension, making difficult the arrival of some species. This does not mean that species do not arrive, but that they may be late arriving at local assemblage. However recent studies in aquatic environments have found a considerable relation between the body size and dispersion capacity of the organisms, and smaller individuals would be easier to disperse compared to large individuals. The high fraction unexplained by any of the variables can occur perhaps by not including in the model non-measured environmental variables, by historical factors or only by events of competition interactions and local extinctions with no relation to environmental conditions. This work contributed to new knowledge of the ecological factors considered important for structuring the phytoplankton assembly in the reservoir. Mainly regarding spatial distance as a structuring factor that influences the distribution of small-sized organisms such as phytoplankton.